Deciphering the link between procurement systems and sustainable building success in Hong Kong. Issue 5 (6th November 2019) - Tang, Ziwei; Ng, S Thomas; Skitmore, Martin
Abstract : Sustainable buildings are regarded as one of the most effective approaches to saving resources, reducing greenhouse gas emissions and supporting sustainable development. In the absence of prior research, Delphi as a group model-building approach for building a system dynamics model is appropriate for capturing the knowledge of construction professionals to identify the relationship between procurement systems and sustainable building success by facilitating efficient group communication. The concepts of the Delphi method were reviewed. Two rounds of Delphi questionnaires were carried out to identify the causal relationships between procurement system variables, critical success factors and success criteria. A causal-loop diagram was built based on the results of the two rounds of Delphi study; this will serve as a basis for building a system dynamics model of sustainable building success in a future study. The results show that some critical success factors related to sustainable building in Hong Kong include 'market planning/business case for sustainability as sustainable objectives'; 'top management commitment and support'; 'sustainable strategic planning'; 'green timing: early evaluation and adoption of sustainability considerations'; and 'training and education'.